A base pair resolution map of nucleosome positions in yeast - Brogaard, Kristin (2012)
The exact positions of nucleosomes along genomic DNA can influence many aspects of chromosome function, yet existing methods for mapping nucleosomes do not provide the necessary single base pair accuracy to determine these positions. Here we develop and apply a new approach for direct mapping of nucleosome centers based on chemical modification of engineered histones. The resulting map locates nucleosome positions genome-wide in unprecedented detail and accuracy. It reveals novel aspects of the in vivo nucleosome organization that are linked to transcription factor binding, RNA polymerase pausing, and the higher order structure of the chromatin fiber.